Korelasi Pra-Pemahaman Gadamer Dengan Syarat Dan Adab Mufassir - Muhammad Aminullah (Rahmad : Jurnal Studi Islam dan Ilmu Al-Qur'an, 2023)
This research aims to reveal the correlation between Gadamer's pre-understanding and mufassir terms and manners. This type of research is qualitative in the form of library research. The approach used is an interpretive approach. The data used is primary data sourced from books and scriptures, and secondary data includes related works and other references that can support research, which are then processed and analyzed. The results of the research show that in the dialectical process, an interpreter must have a pre-understanding that already exists and is formed within him, in the form of art, history, world view, experience, sharpness of mind, the external world, spirituality, expressions, styles, and symbols. However, according to Gadamer, pre-understanding must be criticized so that it does not go beyond the meaning of the text, so that what he calls "perfect understanding" will be formed. With Gadamer's concept of pre-understanding, the relationship between hermeneutics and interpretation can be seen from a different perspective, in the sense of not seeing hermeneutics as a whole. There are basic similarities, so that the goals to be achieved both lead to a good interpretation process and are in accordance with the meaning of the text itself. This can be seen from the points contained in the concept of pre-understanding the terms and adab of mufassir as the initial foundation before interpreting the text of the Koran. The knowledge that a pre-understanding interpreter has regarding the sciences of the Qur'an when he wants to interpret the Qur'an is very important, because these sciences play a very important role when an interpreter has a dialogue with the text, so that in the end he produces a correct interpretation. really good, according to the meaning of the text.